War and the Engineers : The Primacy of Politics over Technology - Lieber, Keir A. (Cornell University Press, 2018)
Do some technologies provoke war? Do others promote peace? Offense-defense theory contends that technological change is an important cause of conflict: leaders will be tempted to launch wars when they believe innovation favors attackers over defenders. Offense-defense theory is perhaps best known from the passionate and intricate debates about first-strike capability and deterrence stability during the cold war, but it has deeper historical roots, remains a staple in international relations theorizing, and drives modern arms control policymaking.In War and the Engineers, the first book systematically to test the logical and empirical validity of offense-defense theory, Keir A. Lieber examines the relationships among politics, technology, and the causes of war. Lieber's cases explore the military and political implications of the spread of railroads, the emergence of rifled small arms and artillery, the introduction of battle tanks, and the nuclear revolution. Lieber incorporates the new historiography of World War I, which draws on archival materials that only recently became available, to challenge many common beliefs about the conflict. The author's central conclusion is that technology is neither a cause of international conflict nor a panacea; instead, power politics remains paramount.
Keywords: Military art and science -- Political aspects -- Case studies.; Military art and science -- Technological innovations -- History -- 19th century -- Case studies.; Military art and science -- Technological innovations -- History -- 20th century -- Case studies.; Military weapons -- History -- 19th century -- Case studies.; Military weapons -- History -- 20th century -- Case studies.; Security, International -- History -- 19th century -- Case studies.; Security, International -- History -- 20th century -- Case studies.; Military History.; Security Studies.; Art et science militaires -- Aspect politique -- Études de cas.; Armes de guerre -- Histoire -- 20e siècle -- Études de cas.; Armes de guerre -- Histoire -- 19e siècle -- Études de cas.; Art et science militaires -- Innovations -- Histoire -- 20e siècle -- Études de cas.; Art et science militaires -- Innovations -- Histoire -- 19e siècle -- Études de cas.; POLITICAL SCIENCE / Security (National & International).; Military art and science -- Political aspects.; Military art and science -- Technological innovations.; Military weapons.; Security, International.; 1800-1999; Case studies.; History.